Volcanic trigger of ocean deoxygenation during Cordilleran ice sheet retreat - Du, Jianghui; Mix, Alan C.; Haley, Brian A.; Belanger, Christina L.; Sharon (Nature, 2022)
North Pacific deoxygenation events during the last deglaciation were sustained over millennia by high export productivity, but the triggering mechanisms and their links to deglacial warming remain uncertain1–3. Here we find that initial deoxygenation in the North Pacific immediately after the Cordilleran ice sheet (CIS) retreat4 was associated with increased volcanic ash in seafloor sediments. Timing of volcanic inputs relative to CIS retreat suggests that regional explosive volcanism was initiated by ice unloading5,6. We posit that iron fertilization by volcanic ash7–9 during CIS retreat fuelled ocean productivity in this otherwise iron-limited region, and tipped the marine system towards sustained deoxygenation. We also identify older deoxygenation events linked to CIS retreat over the past approximately 50,000 years (ref. 4). Our findings suggest that the apparent coupling between the atmosphere, ocean, cryosphere and solid-Earth systems occurs on relatively short timescales and can act as an important driver for ocean biogeochemical change.
Keywords: Marine chemistry; Palaeoceanography